Who disapproves of TTIP? Multiple distrust in companies and political institutions - Österreichisches Institut für Wirtschaftsforschung, Vienna; Pitlik, Hans (Vienna, 2016)
"In 2013, EU and USA initiated a new political dialogue regarding a further deepening of bilateral trade and investment relations, the TTIP (Transatlantic Trade and Investment Partnership). In some EU member countries, anti-TTIP street protests and political activists received substantial support. The paper is concerned with the drivers of public support or disapproval of TTIP. In particular, we focus on the role of (dis-)trust in companies and in political institutions for attitude formation concerning economic regulation. We use data from a Eurobarometer Survey conducted in November 2014 to assess the determinants of individual approval or disapproval of TTIP by European citizens. By means of a mixed-level logit regression it can be shown that disapproval is highly correlated with a lack of trust in European institutions and in large companies. Our results moreover indicate that anti-TTIP political activism has a strong impact on TTIP-related preferences."